The Role of Cell Adhesion and Cytoskeleton Dynamics in the Pathogenesis of the Ehlers-Danlos Syndromes and Hypermobility Spectrum Disorders - Malek, Sabeeha; Köster, Darius V. (Frontiers in Cell and Developmental Biology, 2021)
The Ehlers-Danlos syndromes (EDS) are a group of 13 disorders, clinically defined through features of joint hypermobility, skin hyperextensibility, and tissue fragility. Most subtypes are caused by mutations in genes affecting the structure or processing of the extracellular matrix (ECM) protein collagen. The Hypermobility Spectrum Disorders (HSDs) are clinically indistinguishable disorders, but are considered to lack a genetic basis. The pathogenesis of all these disorders, however, remains poorly understood. Genotype-phenotype correlations are limited, and findings of aberrant collagen fibrils are inconsistent and associate poorly with the subtype and severity of the disorder. The defective ECM, however, also has consequences for cellular processes. EDS/HSD fibroblasts exhibit a dysfunctional phenotype including impairments in cell adhesion and cytoskeleton organization, though the pathological significance of this has remained unclear. Recent advances in our understanding of fibroblast mechanobiology suggest these changes may actually reflect features of a pathomechanism we herein define. This review departs from the traditional view of EDS/HSD, where pathogenesis is mediated by the structurally defective ECM. Instead, we propose EDS/HSD may be a disorder of membrane-bound collagen, and consider how aberrations in cell adhesion and cytoskeleton dynamics could drive the abnormal properties of the connective tissue, and be responsible for the pathogenesis of EDS/HSD.